Predictive Value of Pulse Pressure in Acute Ischemic Stroke for Future Major Vascular Events. Issue 1 (January 2018) - Lee, Keon-Joo; Kim, Beom Joon; Han, Moon-Ku; Kim, Joon-Tae; Cho, Ki-Hyun; Shin, Dong-Ick; Yeo, Min-Ju; Cha, Jae-Kwan; Kim, Dae-Hyun; Nah, Hyun-Wook; Kim, Dong-Eog; Ryu, Wi-Sun; et al.
Abstract : Background and Purpose—: This study aimed to investigate whether pulse pressure (PP) obtained during the acute stage of ischemic stroke can be used as a predictor for future major vascular events. Methods—: Using a multicenter prospective stroke registry database, patients who were hospitalized for ischemic stroke within 48 hours of onset were enrolled in this study. We analyzed blood pressure (BP) data measured during the first 3 days from onset. Primary and secondary outcomes were time to a composite of stroke recurrence, myocardial infarction, all-cause death, and time to stroke recurrence, respectively. Results—: Of 9840 patients, 4.3% experienced stroke recurrence, 0.2% myocardial infarction, and 7.3% death during a 1-year follow-up period. In Cox proportional hazards models including both linear and quadratic terms of PP, PP had a nonlinear J-shaped relationship with primary (for a quadratic term of PP, P =0.004) and secondary ( P <0.001) outcomes. The overall effects of PP and other BP parameters on primary and secondary outcomes were also significant ( P <0.05). When predictive power of BP parameters was compared using a statistic of −2 log-likelihood differences, PP was a stronger predictor than systolic BP (8.49 versus 5.91; 6.32 versus 4.56), diastolic BP (11.42 versus 11.05; 10.07 versus 4.56), and mean atrial pressure (8.75 versus 5.91; 7.03 versus 4.56) for the primary and secondary outcomes, respectively. Conclusions—: Our study shows that PP when measured in the acute period of ischemic stroke has nonlinear J-shaped relationships with major vascular events and stroke recurrence, and may have a stronger predictive power than other commonly used BP parameters. Abstract : Supplemental Digital Content is available in the text.